Estudo das cônicas através de roteiros didáticos aplicados no GeoGebra - Vaz, Nercionildo Pereira (2014)
To teach classes on the conic 3rd year of high school, always observed that most students did not recall the main de nitions, and had great di culty. To improve learning this, think of a proposed intervention that did the student work in a more pleasant way this content. With the advent of computing and software GeoGebra, elaborate didactic itineraries practices, so that they could revise and deepen the main concepts of conic. This work was then developed in order to make the students could visualize and deepen the knowledge previously studied in books, aiming at a better xation of the content. It is designed with questions, so that students examine the de nitions, discuss the results, and from there to better understand the content, and know a little of the appearance, the history and evolution of knowledge on conic.